CONVERGING FINTECH AND MARKETING TECHNOLOGY: AN INTEGRATED FRAMEWORK FOR AI-DRIVEN CUSTOMER ACQUISITION AND LIFETIME VALUE OPTIMIZATION IN DIGITAL-FIRST FINANCIAL SERVICES - Abhay Sahukar; Harshvardhan M; Basavaraj; Naina; Vishwajeet (International Educational Journal of Science and Engineering, 2026)
The convergence of Financial Technology (FinTech) and Marketing Technology (MarTech) represents one of the most structurally significant shifts in how financial services firms acquire, engage, and retain customers. While these two domains have historically operated in separate organizational silos — the former governed by compliance and product engineering, the latter by brand and growth teams — the proliferation of real-time data infrastructure, AI-driven decisioning engines, and open banking standards has created the conditions for deep integration. This paper develops an integrated framework that maps the architectural, economic, and behavioural dimensions of FinTech-MarTech convergence. Using a mixed-method approach combining systematic literature review, analysis of secondary market data from 2020 to 2024, and case analysis of three digital-first financial firms operating in India, Southeast Asia, and the United Kingdom, we demonstrate that firms with tightly integrated FinTech-MarTech stacks achieve a 23–38% reduction in customer acquisition cost (CAC) and a 19–31% improvement in 12-month net revenue retention (NRR) relative to firms with siloed architectures. We further identify three critical enablers — unified Customer Data Platforms (CDPs), compliant AI personalization layers, and real-time attribution infrastructure — whose joint presence is necessary but not sufficient without corresponding organizational redesign. We conclude by proposing a Maturity Model for FinTech-MarTech Integration (MMFMI) and outline its implications for product strategy, capital allocation, and regulatory design in emerging digital financial markets.